Politics of Desire in the New Economy. From the historical background - Ana Rodríguez Granell; Pau Alsina González (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
This paper aims to analyze the factors related to affectivity, emotions and desire as key elements in the social production of subjectivity and the actual economic dynamics. Its aim to explore is the correspondence between the early critiques to modernity and the current New Economy model. To this end, it will focus on the political economy of creative industries in which the production of desires is understood to be an asset of productivity and it responds to the last capitalist reform. Special emphasis will be placed on how a critical community emerges able to question the contemporary labour conditions, not only to those who work in the vulnerable field of creative work but including a large range of unprotected workers. This analysis will take the form of multiple significant case studies, which will help to show how to suggest an alternative concept of emotion and desire, and how we can recover methods from past artistic avant-gardes and its engagement with social movements that had worked in this direction to create new communities and new political subjects in the contemporary economic context.